Available acid consumption capacity of sediments in six water bodies in the Yangtze River Basin in China. (15th September 2021) - Li, Qingman; Bao, Xu; Chen, Peng; Jiao, Yang; Gu, Sen
Highlights: Procedures to determine available acid consumption capacity (AACC) were developed. Variation magnitude of AACC depended significantly on labile acid-soluble minerals. Sediment AACC in the Yangtze River Basin had high regional variability. Sediment AACC six water bodies were divided into Ca-Mg type and Fe-Al type. Abstract: Acid-base reactivity is a fundamental property of sediments and is responsible for sediments' multiple roles in aquatic ecosystems. However, little information currently exists about the composition, magnitude, and change of the available acid consumption capacity (AACC) of sediments. To optimize reaction conditions, we developed operational procedures to determine AACC using base titration to recover surplus acid in suspensions. We characterized the sediment AACC of Dianchi Lake (DL), Daduhe River (DR), Tuojiang River (TR), Honghu Lake (HL), Wuhan Donghu Lake (DhL), and Taihu Lake (TL) in the Yangtze River Basin, China. The procedure demonstrated that reacting 40 mL 0.1 M HCl with fresh sediments equivalent to 1.0 g dry weight for 4 h and recovering surplus acid in the suspension by NaOH titration to an endpoint pH of 3.0 could determine sediment AACC. Sediment AACC in the Yangtze River Basin had high regional variability. The mean magnitude of AACC among sites was ranked DL > DR > DhL > TR > HL > TL, which is extremely similar to their geographical location from the upper to lower reaches of the Yangtze River Basin. Qualitative results from acid titration curves showed that more components contributed to AACC in DL, DR, TR, and DhL sediments than to those in HL and TL sediments. The correlation between AACC and the total amount of multivalent cations released indicated that AACC depended significantly on labile acid-soluble minerals that contain multivalent cations (Fe 3+, Fe 2+, Ca 2+, Al 3+, Mg 2+, and Mn 2+ ) (p < 0.01). Based on the contribution percentages of multivalent cations to AACC, sediment AACC of six water bodies were divided into two types: Ca-Mg dominated (DL, DR, and TR) and Fe-Al dominated (HL, DhL, and TL). We suggest that sediment AACC complexing with pH can contribute to a better description of the acid-base characteristics of sediments. Graphical abstract: Image, graphical abstract